ANALYSIS OF PROBLEM IN THE AERODYNAMIC SYSTEM OF COTTONSEED LINTERING EQUIPMENT IN COTTON PROCESSING PLANTS - Mamadaliev, Farxodbek (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
The article describes the results of an analytical and experimental study of the existing disadvantages and problems of the aerodynamic systems of removing and transporting fluff from the Sawtooth in 5LP linters, which are practically diluted in cotton cleaning enterprises in the system of cotton textile clusters.